MANAJEMEN KESELAMATAN KERJA PADA PERUSAHAAN INDUSTRI - Rusmardi Rusmardi; Yulfi Desi (Jurnal Teknik Mesin, 2004)
Working accident could not be parried by totally. Planner decision maker and organization might have to consider all aspects of working and health safety on their industrial company. Efficiency, worker ability, equipments and devices condition must be well balanced and harmonic, so that the optimal and safety production processes, can be achieved.